2010
DOI: 10.1590/s1517-83822010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulence genes among bulgarian nosocomial and cystic fibrosis isolates of Pseudomonas aeruginosa

Abstract: The aim of this study was to evaluate the prevalence of some virulence genes among 202 Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients (n=42) and non-CF in-patients (n=160)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
54
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 20 publications
25
54
9
Order By: Relevance
“…The frequency of ExoS toxin (63%) was in agreement with other studies done on various clinical and environmental isolates [2,30,31]. The frequency of the ExoU gene (18%) was similar to that obtained by Feltman et al [31] and Bradbury et al [32], however, it was relatively lower than that reported by Mitov et al [30] with a frequency of 30%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The frequency of ExoS toxin (63%) was in agreement with other studies done on various clinical and environmental isolates [2,30,31]. The frequency of the ExoU gene (18%) was similar to that obtained by Feltman et al [31] and Bradbury et al [32], however, it was relatively lower than that reported by Mitov et al [30] with a frequency of 30%.…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of ExoS toxin (63%) was in agreement with other studies done on various clinical and environmental isolates [2,30,31]. The frequency of the ExoU gene (18%) was similar to that obtained by Feltman et al [31] and Bradbury et al [32], however, it was relatively lower than that reported by Mitov et al [30] with a frequency of 30%. Moreover, the proportion of isolates (9%) having both genes was in agreement with Finnan et al [33] and Mitov et al [30], suggesting that the isolates with dual expression of both genes are increasing compared with earlier studies that showed a low number of such isolates (down to one isolate from a total of 115 isolates) [31].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies have shown a high prevalence of the lasB gene in P. aeruginosa, irrespective of their isolation origin [5,6,24]. The prevalence of ExoS observed in this study shows that the strain of Pseudomonas aeruginosa of animal origin could be involved in tissue destruction; ExoS gene is involved in lung infection and may be important for bacterial dissemination [6,7,24].…”
Section: Discussionmentioning
confidence: 50%